2012
DOI: 10.1002/jor.22125
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐investigator collaboration in orthopaedic surgery research compared to other medical fields

Abstract: An increasing emphasis has been placed across health care on evidence-based medicine with higher level studies, such as randomized trials and prospective cohort studies. Historically, clinical research in orthopaedic surgery has been dominated by studies with low patient numbers from a limited number of surgeons. The purpose of this study was to test our hypothesis that orthopaedics has fewer multi-center collaborative studies as compared to other medical disciplines. We chose three leading journals from gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…18 This is particularly important as it has been shown that orthopaedic surgery and sports medicine lag behind other medical disciplines in the percentage of collaborative, multicenter trials. 5 Up to 40% of the research published in leading general medical journals and 13% to 20% of research in other surgical subspecialty journals was the result of multicenter collaborations 5 compared with the much-improved but still paltry 3.5% over 2011-2013 for AJSM. Collaborative studies have been shown to be cited more often than other types of research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 This is particularly important as it has been shown that orthopaedic surgery and sports medicine lag behind other medical disciplines in the percentage of collaborative, multicenter trials. 5 Up to 40% of the research published in leading general medical journals and 13% to 20% of research in other surgical subspecialty journals was the result of multicenter collaborations 5 compared with the much-improved but still paltry 3.5% over 2011-2013 for AJSM. Collaborative studies have been shown to be cited more often than other types of research.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, underneath the umbrella of evidence-based medicine there exists a wide range of scientific rigor, and several papers have brought to light concerns over the methodological quality of orthopaedics research. 2,3,5,10,13,22,23 Therefore, along with the increase in the quantity of evidence-based orthopaedics research, there has been a shift toward efforts to increase quality as well. 6,8,14,26,30,33 At the time of the last report in AJSM, there was an overall increase in methodological quality from 1991-1993 to 2001-2003, as represented in part by randomized, prospective controlled trials increasing from 2.7% to 5.9% of all analyzed studies over the 10-year period.…”
mentioning
confidence: 99%
“…Meniscal preservation was demonstrated to be associated with a lower incidence of chondrosis pathology in this cohort. Brophy et al 4 found a significant decrease in chondrosis associated with previous meniscal repair versus previous partial meniscectomy ( P = .003) at the time of revision reconstruction. No significant difference was noted in knees without previous meniscal treatment and meniscal repair ( P = .7).…”
Section: Discussionmentioning
confidence: 96%
“…At present, orthopaedic surgery and sports medicine have lagged behind other medical disciplines in the percentage of collaborative, multicenter trials. 5,6,31 Although conducting larger, well-conducted trials may be time-consuming and expensive, the effort will increase the likelihood of producing meaningful and truthful results, with increased collaboration among institutions and appropriate planning. [18][19][20]32 Limitations Limitations of the present study include that the review did not consider trials published in other journals, limiting the generalizability of the results about the trends in the orthopaedic sports medicine literature to the global scientific community.…”
Section: Discussionmentioning
confidence: 99%